Design, fabrication and testing of a power operated jab type paddy dibbler - MAJI G. KRISHNAN; Er. Jippu Jacob (Guide) (Tavanur 1997 Kelappaji College of Agricultural Engineering and Technology)
Design, fabrication and testing of a power operated jab type paddy dibbler
Design, fabrication and testing of a power operated jab type paddy dibbler